Democracy and the Armed Forces: Lessons from the Coups of Egypt in 2013 and Turkey in 2016 - Rofiq, Muhammad (Jurnal Hubungan Internasional, 2016)
This article seeks to comparatively examine the military coups happening both in Egypt in 2013 and Turkey in 2016. Two problems discussed in this paper are: firstly, concerning the trigger causes behind the two coups and, secondly, the reason why those phenomena are different, in which the coup was successful in Egypt and failed in Turkey. In order to answer these questions, this paper reviews some aspects related to social condition and the political turmoil before the coups exploded, ranging from the economic crisis, the autocratic policies, the stance of civil society, until the nature of the armed forces itself. The two military coups indicate that the democratization process in the Moslem world is highly determined by the political actors, in which the most important parts of them is the armed forces, in addition, to be shaped by the doctrine of Islam itselfÂ Tulisan ini menganalisa secara komparatif kudeta militer yang terjadi di Mesir tahun 2013 dan Turki tahun 2016. Dua pertanyaan yang didiskusikan adalah: pertama, terkait dengan faktor yang mendorong terjadinya dua kudeta tersebut, dan kedua, alasan mengapa dua fenomena tersebut berbeda, kudeta berhasil di Mesir dan gagal di Turki. Untuk menjawab dua pertanyaan tersebut, tulisan ini melihat sejumlah aspek yang terkait dengan kondisi sosial dan kekacauaan politik menjelang kudeta, mulai dari krisis ekonomi, kebijakan non-demokratis, sikap masyarakat sipil sampai karakteristik angkatan bersenjata kedua negara. Dua kudeta milter yang terjadi ini menunjukkan bahwa proses demokratisasi di dunia muslim sesungguhnya sangat ditentukan oleh aktor politik, di mana peran terpenting dimainkan oleh angkatan bersenjata, selain itu juga dibentuk oleh doktrin Islam sendiri